140k views
3 votes
Please please help me out with this!!!!!!!

Please please help me out with this!!!!!!!-example-1
User Estee
by
5.6k points

2 Answers

4 votes

Answer:

when x= -7

h(-7) = (-7)^2 -5

= (-1)^2*(7)^2-5

= 1*49-5

= 49-5

=44

Therefore , h(-7)=5

User Mewel
by
5.7k points
4 votes

Answer:

h(- 7) = 44

Explanation:

To evaluate h(- 7) substitute x = - 7 into h(x), that is

h(- 7) = (- 7)² - 5 = 49 - 5 = 44

User Ef Ge
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.